The art of short form content : from concept to color correction - Cook, Bryan, 1976- (Focal Press, 2016)
"The Art of Short Form Content: From Concept to Color Correction is an in-depth examination of the craft of creating short form filmic content - a category which includes television commercials, music videos, television promos, movie trailers, digital billboards, corporate videos, and pretty much anything else with a running time under five minutes. Though short form is an important part of the film industry, itis typically overlooked in books on the art of filmmaking. The Art of Short Form Content fills this industry void by answering the type of questions that working short form content creators deal with every day. As Cook explains, though short form content is limited in duration, it is not limited in quality and message. In this step-by-step, full-color guide you will find: - Interviews with leading short form content creators; - Details on how to create everything from a corporate piece to a Super Bowl spot; -Strategies for how to quickly attract viewer attention to your content; - Extensive information on how to best utilize the craft of film-making in an advertising context; - A comprehensive companion website that can be found at www.focalpress.com/cw/cook"--Provided by publisher